Using Process-Tracing to Evaluate Competing Accounts of Proportional Representation in Belgium - Barzachka, Nina (Politics of the Low Countries, 2025)
Analyses of the historical origins of proportional representation (PR) in Belgium have helped shed light on the origins of electoral systems in Western Europe. Nevertheless, debates over what exactly led to the introduction of PR in Belgium persist. Was it electoral threat, Left existential threat or a combination of these two factors? This article applies the completeness standard for process-tracing and employs theoretical insights from the institutional change literature to evaluate these explanations. It re-examines the historical sources used by the extant scholarship of the Belgian case. It finds that both extra-institutional threat and electoral threat fluctuated over time, interacted with one another and mattered during different points of the electoral system reform process. In 1899, when pure PR was finally introduced, both of these factors played a role.